+0  
 
-1
36
1
avatar

find derivative of y=log of base 7 (Square root(9x+9))

 

I have first use change of base formula 1/2 (ln(9x+9)/ ln7 but then what do I do?  

 

thanks!

Guest May 3, 2018
Sort: 

1+0 Answers

 #1
avatar
+1

Find the derivative of the following via implicit differentiation:
d/dx(y) = d/dx((log(sqrt(9 + 9 x)))/log(7))

The derivative of y is y'(x):
y'(x) = d/dx((log(sqrt(9 + 9 x)))/log(7))

Factor out constants:
y'(x) = (d/dx(log(sqrt(9 + 9 x))))/(log(7))

Simplify log(sqrt(9 x + 9)) using the identity log(a^b) = b log(a):
y'(x) = (d/dx(1/2 log(9 + 9 x)))/log(7)

Factor out constants:
y'(x) = ((d/dx(log(9 + 9 x)))/2)/log(7)

Using the chain rule, d/dx(log(9 x + 9)) = ( dlog(u))/( du) ( du)/( dx), where u = 9 x + 9 and d/( du)(log(u)) = 1/u:
y'(x) = (d/dx(9 + 9 x))/(9 x + 9) 1/(2 log(7))

Simplify the expression:
y'(x) = (d/dx(9 + 9 x))/(2 (9 + 9 x) log(7))

Differentiate the sum term by term and factor out constants:
y'(x) = d/dx(9) + 9 d/dx(x) 1/(2 (9 + 9 x) log(7))
The derivative of 9 is zero:
y'(x) = (9 (d/dx(x)) + 0)/(2 (9 + 9 x) log(7))

Simplify the expression:
y'(x) = (9 (d/dx(x)))/(2 (9 + 9 x) log(7))

The derivative of x is 1:
y'(x) = 1 9/(2 (9 + 9 x) log(7))

Simplify the expression:
y'(x) = 9/(2 (9 + 9 x) log(7))

Factor the numerator and denominator of the right hand side:
y'(x) = 9/(18 (1 + x) log(7))

Cancel common terms in the numerator and denominator:

y'(x) = 1/(2 (1 + x) log(7))   [Courtesy of Mathematica 11 Home Edition]

Guest May 3, 2018

16 Online Users

avatar
New Privacy Policy (May 2018)
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  Privacy Policy